2020
DOI: 10.1101/2020.02.10.941971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astroglial FMRP modulates synaptic signaling and behavior phenotypes in FXS mouse model

Abstract: Fragile X syndrome (FXS) is one of the most common inherited intellectual disability (ID) disorders, in which the loss of FMRP protein induces a range of cellular signaling changes primarily through excess protein synthesis. Although neuron-centered molecular and cellular events underlying FXS have been characterized, how different CNS cell types are involved in typical FXS synaptic signaling changes and behavioral phenotypes is largely unknown. Recent evidence suggests that selective loss of astroglial FMR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…We found that postnatal Fmr1 deletion from astrocytes leads to increased GABA levels in astrocytes but decreased expression of synaptic GABAAR and PV levels. Previous studies have shown reduced expression of astroglial glutamate transporter GLT1 and impaired clearance of extracellular glutamate in astroglial Fmr1 cKO mice that may contribute to enhanced hyperexcitability 28,31,75 . However, whether astrocytic Fmr1 affects GABA-mediated signaling remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that postnatal Fmr1 deletion from astrocytes leads to increased GABA levels in astrocytes but decreased expression of synaptic GABAAR and PV levels. Previous studies have shown reduced expression of astroglial glutamate transporter GLT1 and impaired clearance of extracellular glutamate in astroglial Fmr1 cKO mice that may contribute to enhanced hyperexcitability 28,31,75 . However, whether astrocytic Fmr1 affects GABA-mediated signaling remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Fmr1 KO astrocytes are known to trigger FXS-like changes in WT excitatory neurons [28][29][30] . The enhanced excitability was also linked to reduced levels of glutamate transporter in FMRPdeficient astrocytes and reduced glutamate uptake by the astrocytes 28,31 . Whether astrocytes contribute to abnormal inhibitory cell development and circuit hyperexcitability by altering GABAergic signaling has not been investigated in FXS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified cytoplasmic FMRP in satellite glial cells of both rodents and chickens as well as FMRP‐containing envelops surrounding AG neurons in chickens. In the brain, astrocyte‐specific loss of FMRP disrupts astrocytic mGluR5 signaling, alters neuronal dendritic and synaptic development, and contributes to cortical hyperexcitability (Jacobs et al., 2010, 2012; Jin et al., 2021; Men et al., 2020). Determining the significance of FMRP expression in satellite glial cells requires functional analyses.…”
Section: Discussionmentioning
confidence: 99%
“…FMRP-deficient astroglia are capable of inducing abnormal dendritic morphology of WT hippocampal neurons in cocultures (Nimchinsky et al, 2001). Loss of FMRP in astroglia also disrupts astroglial mGluR5 signaling (Men et al, 2020) and reduces expression of the major astroglial glutamate transporter GLT1 and glutamate uptake in the cortex of Fmr1 KO mice (Higashimori et al, 2016), and exhibits several FXS-relevant behavior changes (Jin et al, 2021). As an RBP that is expressed in astroglia, whether FMRP is involved in regulating the localization and expression of mRNAs at astroglial processes is unknown.…”
Section: Introductionmentioning
confidence: 99%